The Pattern of Skin & Venereal disorders among patients attending in the OPD of Dermatology & Venereology Department of a tertiary care private hospital, Dhaka, Bangladesh. - Alam, Mohd Nurul; Husain, Md Anwar; Quarashi, Md Shafiul Alam (Bangladesh Journal of Medical Science, 2017)
Background :It is generally agreed that pattern of skin & venereal diseases differ in different countries and within various regions of a country depending upon social, economic , racial & environmental factor. The morbidity associated with skin and venereal diseases makes them an important public health problem. Very scanty literature is found on the problem which is either disease based, community based or specified population group based. Objective : To assess the pattern of skin and venereal diseases in patients in urban Bangladesh and to determine their relation with demographic character. Materials and method: It is a descriptive study conducted at dermatology and venereology OPD in Ibn Sina Medical College Hospital, Dhaka for the period from 1st January, 2015 to 31st December 2015. Six thousand and two hundred and three patients were enrolled during the study period. The study population comprised of newly diagnosed cases as well as relapsing cases presenting in the outpatient irrespective of gender and age. Diagnosis was made on clinical basis. Lab investigations were restricted to the cases where it carried diagnostic importance. The data was collected through pre-designed questionnaire and analyzed through Microsoft SPSS. Results: Study was conducted on 6203 patients comprising 3373 (54.38%) males and 2830 (45.62%) females, who attended skin and VD OPD of Ibn Sina Medical College during the period of one year. Males were found to be most commonly affected. Male female ratio is 1.2 : 1. Age group between 15 to 29 years carried maximum incidence (43.79%). All disorders were broadly classified into noninfective (63.5%), infective (20.2%) and miscellaneous dermatoses (16.2%) . Eczema 1721 (27.7%) and fungal infections 694 (11.2%) came out to be the two top most common cause for OPD attendances. Conclusion: Our study found a higher prevalence of non-infective dermatoses than infective dermatoses. Eczema and fungal infections formed the largest group in their respective categories. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.354-357